2000
DOI: 10.1016/s0008-6363(00)00140-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of α and β integrins during terminal differentiation of cardiomyocytes

Abstract: These results suggest that progression through the cardiomyocyte cell cycle may be dependent upon cell attachment via integrin beta1 and correlate with changes that occur in beta1 spliced variants and their respective alpha isoforms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 44 publications
3
47
1
2
Order By: Relevance
“…In their studies, Ang1 and VEGF were found to mediate endothelial cell adhesion and survival through interactions with integrins. 11,12 Since various kinds of integrins had been proved to express in adult myocardium, 13 interaction of integrins with VEGF 165 or Ang1 might be the first step that VEGF 165 or Ang1 activated the intracellular PI-3K pathway. Integrins can be served as adhesion receptors that transduce biochemical signals into the cell.…”
Section: Discussionmentioning
confidence: 99%
“…In their studies, Ang1 and VEGF were found to mediate endothelial cell adhesion and survival through interactions with integrins. 11,12 Since various kinds of integrins had been proved to express in adult myocardium, 13 interaction of integrins with VEGF 165 or Ang1 might be the first step that VEGF 165 or Ang1 activated the intracellular PI-3K pathway. Integrins can be served as adhesion receptors that transduce biochemical signals into the cell.…”
Section: Discussionmentioning
confidence: 99%
“…␣ 6 is vital to CM function, prevalent on CM, and is not expressed by cardiac fibroblasts. 65 Isoforms (␣ 6A and ␣ 6B ) are expressed in fetal and adult hearts, 36 and levels shift during cardiac development. 66,67 The blocking effects of ␤ 3 and ␣ 6 antibodies support a link between myocyte-Ang1 interactions and activation of cell signaling (Figures 6 through 12).…”
Section: Dallabrida Et Al Angiopoietin-1 Promotes Myocyte Survival E15mentioning
confidence: 99%
“…34 Integrins are also regulated by dynamic spatial and temporal expression patterns 35 and subunit isoforms. For example, integrin adhesion, expression, and activation shift during cardiac development, 36 hypertrophy, 35 infarct, 37 and failure. 38 Information traffic via integrins is bidirectional, enabling cells to interact with the extracellular matrix (ECM)/environment.…”
mentioning
confidence: 99%
“…13,14 This decrease in ␤ 1 integrin expression is also noted in aging mouse myocardium. 6 We found that both RGD and blocking antibodies partially reduced infectivity, implicating the ␤ 1 integrin-RGD interaction as one of the mechanisms involved in the adenoviral infection process in cardiomyocytes in vitro.…”
Section: Discussionmentioning
confidence: 60%
“…12 ␤ 1 integrins are the prime isoform expressed in postnatal cardiac cells, 13 and ␣ 5 is not detected in adult rat cardiac myocytes. 14 To further explore the role of these integrins and determine the mechanism of decreased infectivity seen in aging cardiac myocytes, we (1) tested the efficiency of adenoviruses at mediating gene transfer and expression in aging cardiac myocytes in vitro, (2) extended these observations to another rat model of aging, (3) compared the level of adenovirus receptors and integrin expression (both CAR-dependent and -independent pathways) in aging versus control adult cardiomyocytes, and (4) studied the involvement of integrins in the mechanism of adenovirus infection in cardiomyocytes.…”
mentioning
confidence: 99%